PENGARUH MODEL PEMBELAJARAN KOOPERATIF NHT DAN STAD TERHADAP HASIL BELAJAR PENGETAHUAN BIOLOGI SISWA SMA NEGERI 2 GERUNG - I. G. M. R. Aryana; Agil Al Idrus; Ahmad Harjono (Postgraduate, University of Mataram, 2016)
This study aims to determine differences of knowledge biology student learning outcomes between groups of students who receive NHT cooperative learning model and STAD cooperative learning model treatment for digestive system. This research was conducted at SMAN 2 Gerung in class of XI. This study is a quasi-experimental research using modified of Type Between Group Design with Pre-posttest design. The number of population was 44 students that using simple random sampling in order to obtain two classes of experiments. Data were analyzed using inferential statistical analysis and hypothesis was tested using t-test analysis with SPSS version 20 for Windows. The results showed: First, there was no significant difference about knowledge learning outcome between the group the of students using NHT cooperative learning model and group of students using STAD cooperative learning model in the substance of Food, Food Healthy Menu, Structure and Function of Cells Network of Human Digestive System, Network Structure System of Ruminant Digestion, and Digestive Disorders Bioprocess Systems that gained tcount ≤ ttable (p> 0.05). Second, a group of students using STAD cooperative learning model has an average value of knowledge learning outcome that is significantly higher than the group of students that use NHT cooperative learning model for Body Mass Index (BMI) and Basal Metallic Rate (BMR) that gained value ttable < tcount (p ≤ 0.05).Keyword: NHT cooperative learning model, STAD cooperative learning model, student’s knowledge learning outcome of biology